Pengaruh Perencanaan Produksi Dan Pengendalian Produksi Terhadap Kualitas Produk - Ali Mutaufiq; Suherman (Jurnal Ekonomi dan Bisnis, 2021)
This study aims to examine and analyze the effect of planning and production control on product quality of PT. Indonesian Kojin. Data was collected through distributing questionnaires to 44 respondents at PT. Indonesian Kojin. The sampling technique uses the probability sampling method, which is based on respondents who are in the production and quality department at PT. Indonesian Kojin. Hypothesis testing conducted using t test shows that the second variable is production planning (X1), production control (X2), which has been proven to significantly affect the variable, namely product quality (X2). Then through the f test, it can be seen that the production planning and production control variables are indeed feasible to test the dependent variable, namely product quality. Adjusted R Square shows that the remaining 94.60% of 5.40% is the contribution of other variables outside of these variables